The Discriminant Analysis on Mortgage Defaults and Decision Making between Commercial Banks and Local Banks: An Application of Decision Making Trial and Evaluation Laboratory - Factor Decomposition Method - Hong, Cheng-Yih; Hsu, Chen-Jung; Wei, Ching-Chun (International Journal of Economics and Financial Issues, 2018)
The financial crisis affected the Taiwanese economy, substantially increasing overdue loans in banks. Since commercial banks (CBs) and local banks (LBs) involve varying operational conditions, the factors contributing to their mortgage defaults might also differ. In addition, differences in organizational and financial structures exist between CBs and LBs. Both types of banks maintain different views regarding loan policies; such views are reflected in operating performance. The present study developed a DEMATEL (Decision Making Trial and Evaluation Laboratory)-FDM (Factor Decomposition Method) that could structuralize mortgage defaults to further investigate the extent of the gap between various key factors. Keywords: Mortgage Defaults, Commercial Banks, Local Banks, DEMATEL- FDM JEL Classifications: G01, G32, G41